Implementasi Secure Storage Menggunakan Metode Full Disk Encryption dan Tamper Proof pada Cloud Storage - Barok Rizqi; Andriani Adi Lestari (Politeknik Siber dan Sandi Negara, 2023)
Currently, storage development has shifted to internet-based storage, or cloud storage, as online storage media. Cloud storage is becoming more popular among the public due to several advantages, including the fact that when the storage on personal computers runs out, users do not need to purchase new storage devices or incur additional costs for device maintenance. However, using such online storage can increase risks such as unauthorized access, data leakage, sensitive data, and privacy rights. This study proposes a prototype secure personal cloud storage system with physical database protection. The device has data encryption features that use full disk encryption to secure data on the server, VPN to secure communication between user and server, and tamper proof to physically secure the database. The test results show that the implementation of secure storage affects the performance of cloud storage, as evidenced by the decrease in data write speed from 19.87 Mb/s to 15.75 Mb/s after the implementation of LUKS full disk encryption. On the security side of data transmission, OpenVPN can secure the transmission between the user and the server. This is evidenced by sniffing testing using wireshark tools which shows that data transmission has been encapsulated by the OpenVPN application. In unit testing carried out on LUKS, it proved that the number of LUKS version 2 key slots corresponds to the reference, which is a maximum of 32 key slots. The last test proves that the tamper proof mechanism can work as expected. The tamper proof mechanism works when the device detects an indication of an attack on the physical device. The tests carried out were destroying the device casing using a hammer, opening the casing bolt, and a saw. The test results show that the device will perform damage to the SSD when the attack indication exceeds the tolerance value.